Targeted inhibition of mammalian target of rapamycin (mTOR) enhances radiosensitivity in pancreatic carcinoma cells - Dai ZJ; Gao J; Kang HF; Ma YG; Ma XB; Lu WF; Lin S; Ma HB; Wang XJ; Wu WY (Dove Medical Press, 2013)
Zhi-Jun Dai,1,* Jie Gao,2,* Hua-Feng Kang,1,* Yu-Guang Ma,1 Xiao-Bin Ma,1 Wang-Feng Lu,1 Shuai Lin,1 Hong-Bing Ma,1 Xi-Jing Wang,1 Wen-Ying Wu3 1Department of Oncology, 2Department of Nephrology, 3Department of Pharmacology, Second Affiliated Hospital, Medical School of Xi'an Jiaotong University, Xi'an, People's Republic of China*These authors contributed equally to this work Abstract: The mammalian target of rapamycin (mTOR) is a protein kinase that regulates protein translation, cell growth, and apoptosis. Rapamycin (RPM), a specific inhibitor of mTOR, exhibits potent and broad in vitro and in vivo antitumor activity against leukemia, breast cancer, and melanoma. Recent studies showing that RPM sensitizes cancers to chemotherapy and radiation therapy have attracted considerable attention. This study aimed to examine the radiosensitizing effect of RPM in vitro, as well as its mechanism of action. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and colony formation assay showed that 10 nmol/L to 15 nmol/L of RPM had a radiosensitizing effects on pancreatic carcinoma cells in vitro. Furthermore, a low dose of RPM induced autophagy and reduced the number of S-phase cells. When radiation treatment was combined with RPM, the PC-2 cell cycle arrested in the G2/M phase of the cell cycle. Complementary DNA (cDNA) microarray and reverse transcription polymerase chain reaction (RT-PCR) revealed that the expression of DDB1, RAD51, and XRCC5 were downregulated, whereas the expression of PCNA and ABCC4 were upregulated in PC-2 cells. The results demonstrated that RPM effectively enhanced the radiosensitivity of pancreatic carcinoma cells. Keywords: radiation; pancreatic carcinoma; mTOR; rapamycin